THE EFFECT OF IMPLEMENTING A CLINICAL PATHWAY FOR TYPHOID FEVER ON QUALITY AND COST CONTROL AT MITRA MEDIKA PREMIERE HOSPITAL, MEDAN - Harahap, Fahri Parlaungan; Fitriani, Arifah Devi; Theo, Deli (HEARTY, 2026)
The implementation of Clinical Pathways (CP) is a key strategy to improve healthcare quality while controlling costs through standardized and evidence-based services. Typhoid fever is one of the most common inpatient diagnoses, requiring effective and efficient clinical management. Mitra Medika Premiere Hospital Medan has implemented a Typhoid Fever Clinical Pathway as part of its quality and cost control efforts. This study aims to analyze the implementation of the Typhoid Fever Clinical Pathway as a quality and cost control instrument and to identify factors influencing its implementation. This study employed a qualitative approach, with data collected through interviews, observations, and document reviews involving healthcare professionals engaged in CP implementation. The findings indicate that healthcare providers demonstrate good knowledge and positive attitudes toward CP and understand its benefits in improving service organization and efficiency. CP dissemination has been conducted across units and is supported by adequate human resources and medical facilities. However, the implementation has not been fully optimal due to challenges such as inconsistent documentation compliance, high workload, multiple patient diagnoses, comorbidities, and suboptimal inter-unit coordination and evaluation mechanisms. In conclusion, the hospital has adequate resources and infrastructure to support the implementation of the Typhoid Fever Clinical Pathway. However, strengthening supervision, regular training, and improving evaluation mechanisms are necessary to optimize its implementation and achieve quality improvement and cost efficiency.